A modified Coffin-Manson model for ultra-low cycle fatigue fracture of structural steels considering the effect of stress triaxiality. (1st October 2020) - Li, Shuailing; Xie, Xu; Cheng, Cheng; Tian, Qin
Highlights: A modified Coffin-Manson model considering the effect of stress triaxiality is proposed. The parameters of the proposed model for Q345qC steel are calibrated. The prediction accuracy of the proposed model is verified based on test results. Abstract: The ductile crack initiation of structural steels due to ultra-low cycle fatigue (ULCF) loading often governs the limit state in steel structures. This paper proposes a modified Coffin-Manson model for ULCF fracture of structural steels considering the effect of stress triaxiality. To this end, tests on coupon specimens and circular notched specimens made of Chinese Q345qC steel were conducted to form different stress triaxiality states. Based on test results and corresponding finite element analysis, the parameters of modified Coffin-Manson model were determined, and empirical formulas were established between model parameters and stress triaxiality. Finally, detailed finite element analysis was conducted on circular notched specimen tests to validate the proposed model. The results show that the proposed model can be used to predict ULCF fracture of structural steels at different stress triaxialities with high accuracy.